Performance of business groups: evidence from port-crisis Russia - Andrei Shumilov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
Transition economies like Russia lack properly functioning financial markets and institu-tions, which results in severe agency and information problems. Business groups in such markets have the potential to offer benefits to member firms, but they also may destroy value. Using a unique database on membership in Russian business groups, we analyze the relationship between group affiliation and firm performance on the basis of a large panel of manufacturing firms for the period 1999-2002. We find that group membership has a posi-tive effect on productive efficiency, but gains from improved productivity in group affili-ates do not adequately translate into higher profitability. This is consistent with the expro-priation hypothesis, according to which controlling owners of groups extract private bene-fits by siphoning profits from their members. Among the different group categories deli-neated by type of controlling owner, the extent of profit dissipation is especially large in groups controlled by private domestic owners, who face a greater risk of possible future expropriation of property. Finally, we examine two potential sources of benefits of mem-bership in business groups: mutual insurance among affiliated firms and preferential treat-ment from the state via subsidies and tolerated tax arrears. We find that, during the period studied, groups neither provided mutual insurance nor did they receive larger support from the state than unaffiliated firms. Together with findings from the previous literature indi-cating that, prior to the 1998 financial crisis, group firms benefited from more efficient al-location of capital within groups than in the rest of the economy but not after the crisis, our results suggest that the advantages of group membership recede as the economic and insti-tutional environment gradually improves.
URN:NBN:fi:bof-201408072147
Keywords: G30; L20; 330; business groups; firm performance; transition economy; Russia